Strategi Pengembangan Bisnis UMKM melalui Pemanfaatan Artificial Intelligence - Andalangi Maatuil, Rexy; Nontje Tangkawarouw; Veine Metusalah; Beverli Arikalang; Fransiska Worotitjan; Zuleika Wuisan (Indo Publishing, 2025)
The utilization of Artificial Intelligence (AI) presents significant strategic opportunities for the advancement of micro, small, and medium enterprises (MSMEs) in the era of rapid digital transformation. AI technologies allow MSMEs to improve operational efficiency, understand customer behavior more accurately, and strengthen data-driven decision-making across various business functions. This study explores several strategies that MSMEs can implement in leveraging AI, including automated customer service through chatbots, real-time market analysis, supply chain optimization, and personalized marketing based on consumer preferences. Through a literature review approach, this article emphasizes that AI adoption not only increases productivity but also enhances the competitiveness of MSMEs within an increasingly dynamic and competitive market landscape. The findings suggest that the effective integration of AI requires strong support in the form of human resource readiness, adequate digital infrastructure, and enabling government policies. These elements are essential to ensuring that AI adoption contributes sustainably to MSME growth and empowers businesses to navigate future technological challenges with greater resilience.